Edukasi Konseling Laktasi Dalam Meningkatkan Pemberian Kolostrum Pada Ibu Nifas di Puskesmas Kassi Kassi - Fadjriah Ohorella; Ani. T Prianti; Mirna (Yayasan Habiburrahman Jamalu Bina Ummat, 2026)
Colostrum is a protective fluid rich in anti-infective agents and high in protein, secreted from the first to the fourth day postpartum. Globally, it is stated that initiating breastfeeding from the first day of life can reduce neonatal mortality by 16%, and by 22% if the infant is breastfed within the first hour of birth.This study aimed to determine the relationship between the knowledge and attitudes of postpartum mothers regarding colostrum administration to newborns at the Kassi-Kassi Public Health Center (Puskesmas).This was a quantitative study with a cross-sectional approach. The population consisted of 30 postpartum mothers, and the sample size was 30, selected using total sampling technique. The research instrument used was a questionnaire. Data were analyzed using the Chi-square test. The results showed a significant relationship between maternal knowledge and colostrum administration (p=0.000), as well as a significant relationship between maternal attitudes and colostrum administration (p=0.05).It is concluded that there is a relationship between maternal knowledge and attitudes toward colostrum administration. It is recommended that mothers who have just given birth provide colostrum to their newborns.